Cell Membrane Coating Technology: A Promising Strategy for Biomedical Applications - Liu, Yao; Luo, Jingshan; Chen, Xiaojia; Liu, Wei; Chen, Tongkai (Nano-Micro Letters, 2019)
Cell membrane coating technology is an approach to the biomimetic replication of cell membrane properties, and is an active area of ongoing research readily applicable to nanoscale biomedicine. Nanoparticles (NPs) coated with cell membranes offer an opportunity to unite natural cell membrane properties with those of the artificial inner core material. The coated NPs not only increase their biocompatibility but also achieve effective and extended circulation in vivo, allowing for the execution of targeted functions. Although cell membrane-coated NPs offer clear advantages, much work remains before they can be applied in clinical practice. In this review, we first provide a comprehensive overview of the theory of cell membrane coating technology, followed by a summary of the existing preparation and characterization techniques. Next, we focus on the functions and applications of various cell membrane types. In addition, we collate model drugs used in cell membrane coating technology, and review the patent applications related to this technology from the past 10 years. Finally, we survey future challenges and trends pertaining to this technology in an effort to provide a comprehensive overview of the future development of cell membrane coating technology. Highlights: 1 The recent progress on using cell membrane-coated nanoparticles for drug delivery, cancer treatment, vascular disease, immune modulation, and detoxification are summarized in this review. 2 The patent applications related to the cell membrane coating technology from the past 10 years are collected, the future challenges and trends pertaining to this technology are comprehensively discussed. 3 Unique properties of cell membrane-coated nanoparticles make it a promising strategy for biomedical applications and will make outstanding contributions to human health.